Attitudes towards seafood and patterns of consumption in an Australian coastal town - McManus, Alexandra; Hunt, W.; Howieson, Janet; Cuesta-Briand, Beatriz; McManus, Jennifer; Storey, Jessica (British Nutrition Foundation, 2012)
Regular seafood consumption plays a protective role against chronic conditions and obesity, which account for the majority of the burden of disease in Australia. Despite public health recommendations, Australians consume less than the recommended levels of omega-3s (n-3) to reduce the risk of chronic disease. The best source of long-chain n-3 is oil-rich fish. This paper reports on results from a community survey on attitudes and patterns of seafood consumption conducted in a coastal town in Western Australia. Data were collected through a self-administered questionnaire and 300 valid responses were received (60.7% aged 55 years or over; 65.7% female). Weekly patterns of seafood consumption were observed. Almost all participants (93.7%) thought seafood was an important part of a healthy, balanced diet. Overall, participants (73.3%) did not perceive seafood as inconvenient to prepare, and had a high level of confidence around cooking and serving seafood. There were no gender or age differences in confidence except for those aged under 30 years with only a third (36.4%) expressing confidence in cooking and serving. All participants, across all ages and genders (78.7–90.7%) made informed decisions when purchasing seafood and they sought more point-of-sale information. They identified affordability, availability, easy-to-understand food labels and quick-and-easy recipes at point of purchase as the main enablers towards increased seafood consumption.